Junctional rhythm during trans-anesthetic monitoring in a goat (Capra aegagrus) with ulcerated neoformation: Case report - Ferraz Cereda Martinez, Júlia; Rizerio Moncayo, Juliana; Almeida Cardoso, Maria Fernanda; Sanches Rosa, Beatriz; dos Santos Souza, Zahi Eni; de Fátima kotleski Thomaz de Lima, Andressa (Pubvet, 2024)
Supraventricular ectopic beats and their rhythms can occur both in the presence and absence of heart disease, secondary to systemic diseases. Its arrhythmogenic mechanisms include enhanced automaticity, triggered activity, and anatomical changes or reentry mechanisms. The junctional region is the normal conduction pathway between atria and ventricles, and can be divided into three segments: atrioventricular node (AVN), Hissian node (HN) and bundle of His. A goat with a neoformation in the vulvar region went through an anesthetic procedure for incisional biopsy, urethral clearance and probing. As pre-anesthetic medication, midazolam (0.2 mg/kg) and morphine (0.1 mg/kg) were administered intravenously, induction with propofol (3 mg/kg), orotracheal intubation and maintenance with isoflurane. Epidural anesthesia was performed in the lumbosacral region with lidocaine (4 mg/kg) and morphine (0.1 mg/kg). Trans-anesthetic monitoring was performed with electrocardiogram (evaluating rhythm and heart rate), pulse oximetry, capnography and invasive mean arterial pressure (MAP), in addition to observing protective reflexes to monitor the anesthetic plane. Upon notice of hypotension and junctional rhythm on the electrocardiogram, 0.04 mg/kg of atropine was administered intravenously (IV), resuming sinus rhythm after application. During the change, no P wave was observed and, after the administration of atropine, the P wave appeared for a few minutes before returning to the junctional rhythm, which was maintained until the end of anesthesia and in the immediate postoperative period.